Women in Leadership: They Persist - Marilyn J Amey; Kristi L Haik; Maria Alm; Christina Lunceford; C. Casey Ozaki; Royce Smith (Academic Chairpersons Conference Proceedings, 2022)
This Spotlight Presentation features the expertise of higher education leaders at different stages of their career. These individuals pursued unique professional pathways within different educational contexts and been exposed to opportunities and challenges calling for a range of problem-solving skills. They will share experiences, what it means to advocate for oneself as a leader, for others, and how to create conditions for sustainable change supporting inclusivity within the complex, shifting landscape of higher education.
Keywords: Leadership; Women Leaders; Inclusivity; Work-life; Advocacy